Potentiation of Tobramycin by Silver Nanoparticles against Pseudomonas aeruginosa Biofilms - Habash, Marc B. (Antimicrob Agents Chemother, 2017)
Increasing antibiotic resistance among pathogenic bacterial species is a serious public health problem and has prompted research examining the antibacterial effects of alternative compounds and novel treatment strategies. Compounding this problem is the ability of many pathogenic bacteria to form biofilms during chronic infections. Importantly, these communities are often recalcitrant to antibiotic treatments that show effectiveness against acute infection. The antimicrobial properties of silver have been known for decades, but recently silver and silver-containing compounds have seen renewed interest as antimicrobial agents for treating bacterial infections. The goal of this study was to assess the ability of citrate-capped silver nanoparticles (AgNPs) of various sizes, alone and in combination with the aminoglycoside antibiotic tobramycin, to inhibit established Pseudomonas aeruginosa biofilms. Our results demonstrate that smaller 10-nm and 20-nm AgNPs were more effective at synergistically potentiating the activity of tobramycin. Visualization of biofilms treated with combinations of 10-nm AgNPs and tobramycin reveals that the synergistic bactericidal effect may be caused by disrupting cellular membranes. Minimum biofilm eradication concentration (MBEC) assays using clinical P. aeruginosa isolates shows that small AgNPs are more effective than larger AgNPs at inhibiting biofilms, but that the synergy effect is likely a strain-dependent phenomenon. These data suggest that small AgNPs synergistically potentiate the activity of tobramycin against P. aeruginosa in vitro and may reveal a potential role for AgNP/antibiotic combinations in treating patients with chronic infections in a strain-specific manner.